Lidar and CTIPe model studies of the fast amplitude growth with altitude of the diurnal temperature "tides" in the Antarctic winter lower thermosphere and dependence on geomagnetic activity. Issue 3 (9th February 2015) - Fong, Weichun; Chu, Xinzhao; Lu, Xian; Chen, Cao; Fuller‐Rowell, Timothy J.; Codrescu, Mihail; Richmond, Arthur D.
Abstract: Four years of lidar observations at McMurdo reveal that the fast amplitude growth with altitude of diurnal temperature tides from 100 to 110 km during Antarctic winters, exceeding that of the freely propagating tides from the lower atmosphere, increases in strength with the Kp magnetic activity index. Simulations with the Coupled Thermosphere Ionosphere Plasmasphere Electrodynamics (CTIPe) model reproduce the lidar observations and exhibit concentric ring structures of diurnal amplitudes encircling the south geomagnetic pole and overlapping the auroral zone. These findings point to a magnetospheric source origin. Mechanistic studies using CTIPe show that the adiabatic cooling/heating associated with Hall ion drag is the dominant source of this feature, while Joule heating is a minor contributor due to the counteraction by Joule‐heating‐induced adiabatic cooling. The sum of total dynamical effects and Joule heating explains ~80% of the diurnal amplitudes. Auroral particle heating, lower atmosphere tides, and direct solar heating have minor contributions. Key Points: CTIPe model reproduces lidar‐observed fast height growth of diurnal temperature tides Tidal amplitudes due to ionospheric convection maximize near polar‐cap boundary Temperature tides are generated by Hall‐ion‐drag‐induced adiabatic effects